The effect of dietary approaches to stop hypertension and ketogenic diets intervention on serum uric acid concentration: a systematic review and meta-analysis of randomized controlled trials - Sepehr Gohari; Saeed Ghobadi; Alireza Jafari; Hassan Ahangar; Sheida Gohari; Mahsa Mahjani (Scientific Reports, 2023)
Abstract Hyperuricemia as a risk factor for metabolic diseases is proved to be profoundly modified by dietary approaches. This systematic review and meta-analysis of randomized control trials (RCT) was conducted to investigate the effect of two nutritional interventions; dietary approaches to stop hypertension (DASH) diet and ketogenic diet (KD) on serum uric acid (UA) concentrations. Our systematic search was for RCTs in which KD or DASH diet were assigned to adults for at least 2 weeks or more. Until March 2023 in Embase, Web of Science, PubMed, and Scopus databases, 10 eligible RCTs that intervened with DASH diet (n = 4) or KD (n = 6) and had provided laboratory data on serum UA were found. Summary effect was calculated by random-effects model. Results from the meta-analysis of the 4 DASH diet RCTs with a total of 590 participants revealed significant decrease in serum UA after at least 4 weeks of interventions (mean difference (MD) = ‒0.25; 95% CI ‒0.4 to ‒0.1 mg/dL; p < 0.01; I2 = 0%). The pooled meta-analysis of the 6 included RCTs of KD reporting data of 267 participants showed no significant changes in serum UA (MD = 0.26; 95% CI ‒0.47 to 0.98 mg/dL, I2 = 95.32%). However, a non-significant reduction of UA in the subgroup analysis of very low-calorie KD (VLCKD) studies (MD = ‒0.04; 95% CI ‒0.29 to 0.22, I2 = 0%) was obtained. DASH diet has an ameliorating effect on serum UA and may be recommended for hyperuricemia states such as gout. In addition, we have shown that serum UA level following KD remained unchanged. Although, in view of the heterogeneity across the studies, further investigations are needed to determine the effect of KD and VLKD on serum UA concentrations.